2014
DOI: 10.1089/acm.2013.0088
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids as Aldose Reductase Inhibitors, with Special Reference to Berberine

Abstract: Aldose reductase is the rate-limiting enzyme of the polyol pathway that leads to conversion of glucose to sorbitol. Its increased activity, which results in abnormal activation of the polyol pathway, is implicated in the development of long-term complications of diabetes mellitus. Different plant species and their active components have shown potent in vitro and in vivo aldose reductase inhibitory activity. Among different phyto-constituents, alkaloids that contain isoquinoline/bis(isoquinoline)and related rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Zhou et al screened for α -glucosidase inhibitors, five components in the RC extract were found, and their structures were identified by electrospray ionization tandem mass spectrometry (ESI-MS) to be COP, epiberberine, JAT, BBR, and PAL [ 51 ]. Aldose reductase (AR) is the enzyme that leads to conversion of glucose to sorbitol, and its increased activity signifies in the development of long-term complications of DM [ 52 ]. Jung et al [ 35 ] evaluated the inhibitory activities of the alkaloids from RC AR for the treatment of diabetic complications.…”
Section: Theoretical Principles Of Using Rcmentioning
confidence: 99%
“…Zhou et al screened for α -glucosidase inhibitors, five components in the RC extract were found, and their structures were identified by electrospray ionization tandem mass spectrometry (ESI-MS) to be COP, epiberberine, JAT, BBR, and PAL [ 51 ]. Aldose reductase (AR) is the enzyme that leads to conversion of glucose to sorbitol, and its increased activity signifies in the development of long-term complications of DM [ 52 ]. Jung et al [ 35 ] evaluated the inhibitory activities of the alkaloids from RC AR for the treatment of diabetic complications.…”
Section: Theoretical Principles Of Using Rcmentioning
confidence: 99%
“…Compared with untreated animals, rats fed with sorbinil displayed 51% and 58% reduction in the ratio of neointima to the media at 10 and 21 days, respectively, after balloon injury [ 155 , 173 ]. Taken together, these findings suggest that AR is upregulated during growth, and that this upregulation facilitates growth by enhancing metabolism of secondary products of ROS [ 30 , 31 , 55 , 56 , 58 ].…”
Section: Introductionmentioning
confidence: 91%
“…[79] Many alkaloids, namely berberine, palmatine, coptisine, and jateorrhizine, possess potent aldose reductase inhibitory potential. [80] The study by Ravindra and Aronstam stated that alongside its effects on tubulin, COL has an inhibitory action on nucleoside transport and aldose reductase activity while increasing adenylate cyclase activity, prostaglandin E2, and cAMP concentrations. [81] Glycation and oxidative stress affect cellular metabolism by perturbing the structural and functional integrity of albumin.…”
Section: Effect Of Col On Cellular Oxidative Stressmentioning
confidence: 99%